Предмет: Алгебра, автор: ChenMin

Упростите выражение cos2a/sin(pi+a)-cos(pi-a)

Ответы

Автор ответа: sedinalana
0
(cosa-sina)(cosa+sina)/(-sina+cosa)=cosa+sina
Автор ответа: xsellizer
0
I-й случай.
cos^2(a) - sin^2(a)/-(sin(a) + cos(a) = (sin^2(a) - cos^2(a) + cos(a)*sin(a)/sin(a) 
= sin(a)(sin(a) + cos(a)) - cos^2(a))/sin(a) =  sin(a)(sin(a) + cos(a)) + sin^2(a) - 1/ sin(a) = sin(a)(sin(a) + cos(a) + sin(a)) - 1/sin(a) = cos(a) + 2sin(a) - sec(a)

II-й случай.
(cosa-sina)(cosa+sina)/(-sina+cosa)=cosa+sina
Похожие вопросы